Inference of stress-strength reliability for two-parameter of exponentiated Gumbel distribution based on lower record values. - Ehsan Fayyazishishavan; Serpil Kılıç Depren (PLoS ONE, 2021)
The two-parameter of exponentiated Gumbel distribution is an important lifetime distribution in survival analysis. This paper investigates the estimation of the parameters of this distribution by using lower records values. The maximum likelihood estimator (MLE) procedure of the parameters is considered, and the Fisher information matrix of the unknown parameters is used to construct asymptotic confidence intervals. Bayes estimator of the parameters and the corresponding credible intervals are obtained by using the Gibbs sampling technique. Two real data set is provided to illustrate the proposed methods.